P PERSEPSI MASYARAKAT TERHADAP KEBERADAAN PETERNAKAN SAPI PERAH DI KELURAHAN KLAMPOK KECAMATAN SANANWETAN KOTA BLITAR - ardi, ardian yonika putro (Universitas Islam Balitar, 2024)
One important part of the Indonesian agricultural industry, including in Blitar City, is dairy farming. Apart from causing many environmental and public health problems, the existence of dairy farms has a significant economic impact on local communities.The aim of this research is to find out public perceptions about the existence of dairy farms in Klampok Village, Sananwetan District, Blitar City. Next, examine the factors that influence public perception about the existence of dairy farming and make policy recommendations based on the results of the analysis of public perception.This research activity was carried out in Klampok Village, Sananwetan District, Blitar City. The method used in this research is a survey method by taking a direct approach to the community around dairy farms in Klampok Village, Sananwetan District, Blitar City. Data was collected in this research using surveys, interviews, questionnaires, observations. Descriptive statistics were chosen to be used in the data analysis of this study.